Classification of CRM systems with knowledge creation approach Case of: Internet Service Provider corp - Seyyed Jamaleddin Hosseini (مدیریت مهندسی و رایانش نرم)
Now a days Customer knowledge is one of the most interesting topics for every organizations in order to gain competitive advantage. Competitive advantage can be achieved through creation of new knowledge. The point is that it is important to know that how information about customers is collected and lead to create new knowledge. In this paper, we consider the levels of support for customer knowledge creation processes by customer relationship management (CRM) in the case. All CRM systems that used in the organization were identified and categorized based on semi-structured interviews with experts in various fields. Then the process of knowledge creation that is created by each system were identified. The survey showed that analytical CRM systems support combination process, operational CRM systems support socialization and externalization processes, and collaborative CRM systems support socialization process. On the other hand, collaborative and analytical CRM systems support internalization process by creating learning opportunities.